Religious Heritage and Nation in Post-Vatican II Catholicism: A View from Quebec - Kaell, Hillary (Religions, 2021)
With Quebec’s croix de chemin (wayside crosses) as a jumping off point, I explore the importance of heritage creation as the province transitioned away from pre-Vatican II Catholicism in the 1960s and 1970s. I include two ‘sites of memory’: fieldwork with contemporary cross caretakers and archival materials from a major government-funded inventory of the crosses in the 1970s. Heritage professionals have generally implied that Catholic objects lose their sacred meaning to become objects of nation-building, while caretakers view them as still-active objects of devotional labour. Regardless, I find that both parties view themselves as laying claim to “modern” ways of interacting with religious objects, while also assuming that a cohesive national identity rests in part on promoting a rural Catholic past. More broadly, I argue that neither side can be fully understood without attention to the convergence of three trends in the 1960s and 1970s: Quebecois and other emergent nationalisms, Catholic liberalization, and the rise of an international heritage industry.